PREGNANT WOMEN’S KNOWLEDGE ABOUT HIGH RISK IN PREGNANCY - Annisa Citrasari Dewi; Ermiati E; Nur Oktavia Hidayati (Journal of Maternity Care and Reproductive Health, 2018)
A high-risk pregnancy is a condition that increases the risk of complications in pregnant women and fetuses compared to normal pregnancies. One key to preventing high-risk in pregnancy is women's knowledge. This study aimed to describe the knowledge of pregnant women about high-risk pregnancies in the PHC Ganeas, Sumedang. The study was a descriptive quantitative research. The number of samples was 146 pregnant women who visited the PHC of Ganeas. The samples were selected using es using stratified random sampling technique. The instrument of this study used a questionnaire consisting of 50 statements. The results showed that 61 respondents (41.0%) were categorized into high-risk pregnancies. The levels of knowledge were  131 respondents (89.7%) had moderate knowledge, 7 respondents (4.8%) had good knowledge, and 8 respondents (5.5%) had insufficient knowledge. The conclusion in this study is that the majority of respondents belong to high-risk pregnancies, and have a moderate level of knowledge. Knowledge of pregnant women in the PHC of  Ganeas should be improved by developing an extension program and information about high-risk pregnancies.Keywords: pregnant women, high-risk pregnancy, knowledge